Recent trends in the determination of polyphenols by electromigration methods - Jác, Pavel; Polásek, Miroslav; Pospísilová, Marie (Journal of pharmaceutical and biomedical analysis, 2006)
An overview mapping recent trends in the determination of polyphenols of natural origin (mostly flavonoids) and their synthetic derivatives by electromigration methods is presented. The overview (covering the period of the recent 5 years and comprising 61 references) is focused on capillary zone electrophoresis (CZE) and micellar electrokinetic chromatography (MEKC) with various detection methods. Techniques comprising on-line pre-separation such as isotachophoresis (ITP)-CZE and flow-injection-CZE, chiral separations and CZE evaluation of antioxidation activity are also discussed.
Keywords: polyfenoly; antioxidancia; Spectrophotometry, Ultraviolet; Electrophoresis, Capillary; Flavonoids; chromatografie micelární elektrokinetická kapilární; Phenols; elektroforéza kapilární; Antioxidants; flavonoidy; fenoly; Chromatography, Micellar Electrokinetic Capillary; spektrofotometrie ultrafialová; Polyphenols